2020
DOI: 10.3390/rs12071113
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impacts of Anthropogenic Activities and Climate Variations on Vegetation Productivity Changes in China from 1985 to 2015

Abstract: Accurate assessment of vegetation dynamics provides important information for ecosystem management. Anthropogenic activities and climate variations are the major factors that primarily influence vegetation ecosystems. This study investigates the spatiotemporal impacts of climate factors and human activities on vegetation productivity changes in China from 1985 to 2015. Actual net primary productivity (ANPP) is used to reflect vegetation dynamics quantitatively. Climate-induced potential net primary productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…Therefore, it is essential to quantify the increasing and decreasing vegetation trends. Climatic variations and anthropogenic activities are the two key driving forces of degradation trends [61]. Several studies have suggested that changing climate is one of the key driving forces of vegetation trends [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to quantify the increasing and decreasing vegetation trends. Climatic variations and anthropogenic activities are the two key driving forces of degradation trends [61]. Several studies have suggested that changing climate is one of the key driving forces of vegetation trends [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Taking the small inter-annual changes in topography into account, changes in precipitation and temperature have profoundly affected the development trend of VNF. The climate of the QTP has developed generally in a warm and humid direction [ 36 ]. The increase in temperature has caused the melting of glaciers and an increase in runoff [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under the combination of climate change and topography, the water retention capacity of forests has also declined [ 51 ]. Therefore, the improvement of soil retention capacity is needed in the regions with higher vulnerability [ 36 , 52 , 53 ]. It is also critical to strengthen the monitoring and prediction of climate changes and consider the impact of climate changes in forest resource assessment, monitoring, investigation, analysis, and long-term planning [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…China has a long history of forest degradation and restoration. To minimize the human impact on the environment and restore vegetation coverage, a series of vegetation-related policies were implemented by China [7]. The largest project is the Three-North Shelter Forest Program (TNSFP), focused on increasing forest cover from 5% to 15% from 1978 to 2050 [8].…”
Section: Of 16mentioning
confidence: 99%
“…A large number of ecological projects were implemented and estimating the effects of these ecological projects became an important research direction. Several studies investigated the spatial and temporal effects of climatic factors and human activities on changes in vegetation productivity from 1985 to 2015, where actual net primary productivity (ANPP) and net primary productivity (NPP) were often used to quantify vegetation dynamics [3,7]. Several studies used multiple satellite images to assess the changes of the leaf area index (LAI), gross primary productivity (GPP), Normalized Difference Vegetation Index (NDVI), and aboveground biomass in different regions in China [10,11].…”
Section: Of 16mentioning
confidence: 99%